Government Policy on Islamic Religious Education in Madrasahs - Adek Kholijah Siregar; Faridi Faridi; Tobroni Tobroni (Badan Penerbit STIEPARI Press, 2025)
The purpose of this study is to analyze government policies in Islamic Religious Education in Madrasahs and to analyze the obstacles and challenges in implementing government policies in Islamic Religious Education in Madrasahs. This research method uses a qualitative approach. This type of research is library research or literature review. Data collection techniques are carried out through observation and documentation. The data sources in this study are primary data and secondary data. The results of this study are that government policies in Islamic Religious Education in Madrasahs are based on, among others: Joint Decree (SKB) Number 6/1975 and Number 037/U/1975 between the Minister of Religion, Minister of Education and Culture, and Minister of Home Affairs concerning Improving the Quality of Education in Madrasahs Law Number 20 of 2003 concerning the National Education System. Law No. 14 of 2005 concerning teachers and lecturers, policies issued by the Minister of Religion in the form of KMA Number 183 of 2019 concerning the PAI Curriculum and Arabic in Madrasahs. 2) Government policy in Islamic religious education in madrasas, namely: issuing Islamic Religious Education laws, creating Islamic Religious Education curriculum, improving the quality of Islamic Religious Education teachers, integrating Islamic Religious Education moderation, creating Islamic Religious Education teaching materials and implementing national exams and assessments in madrasas.